1996
DOI: 10.1128/jb.178.9.2701-2708.1996
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Coxiella burnetii to ampicillin resistance

Abstract: . In the present study, an ars replicon was used to transform C. burnetii to ampicillin resistance. Plasmid pSKO(؉)1000 contained the C. burnetii ars sequence cloned into a ColE1-type replicon encoding ␤-lactamase. pSKO(؉)1000 was introduced into C. burnetii by electroporation. Ampicillin-resistant cells were selected, and survivors were examined for the transformed genotype by Southern hybridization. Transformants stably maintained the pSKO(؉)1000 bla DNA sequence in the chromosome as a result of homologous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 37 publications
2
60
0
Order By: Relevance
“…Previous work demonstrated that the efficacies of chloramphenicol and ciprofloxacin against C. burnetii varied (14,17,25,26), depending on the dose, the culture model, and the C. burnetii strain used to test the antimicrobials. The ability of ampicillin to inhibit C. burnetii growth supports prior evidence presented by Suhan et al (21) that C. burnetii Nine Mile, phase I, is susceptible to ampicillin at 50 g/ml. At present, the recommended treatments for C. burnetii infections involve doxycycline for 2 weeks for acute infections and doxycycline plus chloroquine for at least 18 months for chronic infections.…”
Section: Discussionsupporting
confidence: 74%
“…Previous work demonstrated that the efficacies of chloramphenicol and ciprofloxacin against C. burnetii varied (14,17,25,26), depending on the dose, the culture model, and the C. burnetii strain used to test the antimicrobials. The ability of ampicillin to inhibit C. burnetii growth supports prior evidence presented by Suhan et al (21) that C. burnetii Nine Mile, phase I, is susceptible to ampicillin at 50 g/ml. At present, the recommended treatments for C. burnetii infections involve doxycycline for 2 weeks for acute infections and doxycycline plus chloroquine for at least 18 months for chronic infections.…”
Section: Discussionsupporting
confidence: 74%
“…Similar conditions were optimal for C. trachomatis L2 (data not shown). Small cells such as chlamydial EBs generally require high electric fields for successful transformation, and similar conditions have been reported to be efficient for Coxiella burnetii transformation (17). Tam et al (6) used 10.0 kV/cm, 400 ⍀, and 25 F in their electroporation protocol but reported poor postelectroporation recovery for C. trachomatis L2.…”
Section: Discussionmentioning
confidence: 99%
“…This frequency is presumably an underestimate due to the limitations of the rescue cloning procedure and the possible loss over time of transformants harboring deleterious mutations. Earlier C. burnetii transformation experiments utilized resistance to ampicillin as a method of positive selection (36). However, long-term selection resulted in spontaneous mutation to ampicillin resistance by bacteria lacking the introduced ␤-lactamase gene (36).…”
Section: Discussionmentioning
confidence: 99%
“…Transformation of C. burnetii was described by Suhan et al (36) more than 10 years ago. Using a plasmid containing a 5.8-kb C. burnetii autonomous replication sequence, they transformed C. burnetii to ampicillin resistance (4,35,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation